2009
DOI: 10.3174/ajnr.a1468
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Evaluation of Changes in Extracranial-Intracranial Bypass Graft Using Superficial Temporal Artery Duplex Ultrasonography

Abstract: BACKGROUND AND PURPOSE: Extracranial-intracranial (ECIC) bypass grafts have been assessed postoperatively by various neuroradiologic techniques. The aim of this prospective study was to evaluate postoperative changes in ECIC bypass graft by using superficial temporal artery duplex ultrasonography (STDU). Furthermore, this study assessed the ability of STDU to predict cerebrovascular reserve capacity (CVR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Accordingly, it is advantageous to select an STA or recipient artery with a larger diameter, although caution is required because there is a risk of hemorrhagic cerebral hyperperfusion syndrome if the STA is significantly thicker than the recipient artery [44][45][46][47] . Nakamizo et al reported that the STA diameter and mean STA flow were significantly associated with CVRC, with an STA diameter cutoff value of 1.8 mm 48 . In addition, long-slit arteriotomy and fish-mouth cutting of the donor artery to enlarge the anastomosis site may be helpful 49,50 .…”
Section: Relationship Between Bf and Perfusion Changementioning
confidence: 99%
“…Accordingly, it is advantageous to select an STA or recipient artery with a larger diameter, although caution is required because there is a risk of hemorrhagic cerebral hyperperfusion syndrome if the STA is significantly thicker than the recipient artery [44][45][46][47] . Nakamizo et al reported that the STA diameter and mean STA flow were significantly associated with CVRC, with an STA diameter cutoff value of 1.8 mm 48 . In addition, long-slit arteriotomy and fish-mouth cutting of the donor artery to enlarge the anastomosis site may be helpful 49,50 .…”
Section: Relationship Between Bf and Perfusion Changementioning
confidence: 99%
“…48-51 Nakamizo et al reported that the STA diameter and mean STA ow were signi cantly associated with cerebrovascular reserve capacity, with an STA diameter cutoff value of 1.8 mm. 49 In addition, long-slit arteriotomy and sh-mouth cutting of the donor artery to enlarge the anastomosis site may be helpful. 50,51 Furthermore, according to Poiseulle's law, to reduce resistance, the length of the STA should be minimized to within the distance from the recipient artery as much as possible, which will contribute to increasing bypass ow.…”
Section: Relationship Between Bypass Ow and Perfusion Changementioning
confidence: 99%